Tender Law with Its Executive Regulations. - Egypt; The middle east library for economic services, translator. (2025)
Law No. 89 of the year 1998: Promulgating the Law on organizing tenders and bids. Part 1: On the purchase of movables, contracting on contracting works and acceptance of services Part – 2 On the purchase and rental of real estates. Part -3 On the sale and rental of the real estates, movables and projects and authorizing the use and exploitation of real estates. Part -4: General provisions. Ministerial Decree No. 1367 Of The Year 1998: Concerning the promulgation of the executive regulations of the law on organizing tenders and bids.. Part- 1:Purchase of movables and concluding deals for contracting works as well as receiving services under contract. Section: 1 Preliminary Procedures Section 2 Contracting Procedures. Chapter - 1 General Adjudication. - Chapter - 2-Limited Adjudication. - Chapter 3 Local Adjudication - Chapter - 4 General Practice (Negotiation). - Chapter 5 Limited Practice (Negotiation) - Chapter 6 Direct Agreement. Section: 3 General Conditions. Chapter 1 General Conditions. - Chapter 2 Bid and Performance Bonds. Section: 4 Contracts Execution Procedures - Chapter 1 General Conditions - Chapter 2 Conditions of Implementing the Work Contracting Deeds. - Chapter 3 Conditions for Implementation of Supply Contracts - Chapter 4 Receiving the items. Part -2: Purchasing and Renting Realties. Part-3: Sale and Lease of Realties and Movables and Licensing the Use or Exploitation of Realties. Part-4:General provisions.